2019
DOI: 10.1055/s-0038-1675550
|View full text |Cite
|
Sign up to set email alerts
|

Chondroid Tumors as Incidental Findings and Differential Diagnosis between Enchondromas and Low-grade Chondrosarcomas

Abstract: Chondroid tumors are a heterogeneous group of neoplasms that all share the production of chondroid matrix. This ranges from a fetal type to mature hyaline cartilage and mirrors its imaging characteristics.The benign chondroid tumors represent some of the most encountered incidental bone lesions, with osteochondroma the most frequent benign bone tumor. Enchondroma is mostly asymptomatic, and yet it is probably the second most common primary bone tumor. Similarly, its malignant counterpart, chondrosarcoma, is th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
23
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(24 citation statements)
references
References 56 publications
0
23
0
1
Order By: Relevance
“…Cartilaginous tumors commonly have morphological heterogeneity and can have focal high-grade areas [ 21 ]. Consequently, there are risks of sampling failure of high-grade tumor tissue in a predominantly benign or low-grade lesion, and of under- or over-grading the tumors [ 22 , 23 ]. Compared with other types of bone tumors, high rates of discrepancies between biopsy findings and final diagnoses were reported in cartilaginous tumors [ 3 , 5 , 7 , 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Cartilaginous tumors commonly have morphological heterogeneity and can have focal high-grade areas [ 21 ]. Consequently, there are risks of sampling failure of high-grade tumor tissue in a predominantly benign or low-grade lesion, and of under- or over-grading the tumors [ 22 , 23 ]. Compared with other types of bone tumors, high rates of discrepancies between biopsy findings and final diagnoses were reported in cartilaginous tumors [ 3 , 5 , 7 , 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…The distinction of enchondroma from the borderline malignancy arising in the appendicular skeleton, the atypical cartilaginous tumor formerly known as grade 1 or low-grade central chondrosarcoma, 12 is problematic both on imaging and pathology. 8 13 14 15 16 Recent studies have highlighted the increased identification of CCTs attributed to the ever-increasing use of MRI particularly in the proximal humerus and around the knee. 17 18 Guidelines and imaging protocols for the management and follow-up have been proposed in an attempt to reduce costly and in many instances diagnostically low-yield follow-up imaging studies.…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, if there were signs of invasion (i.e., cortical bone invasion, periosteal reaction, bone expansion, periostitis, and extraosseous soft tissue), it is very likely that these cartilaginous lesions are chondrosarcomas [2]. In addition, CT scans of other parts of the body, especially the chest, are crucial for conducting a comprehensive staging of patients with chondrosarcoma [1,2]. Promising pooled sensitivity (94%) and specificity (89%) of 18 F-FDG PET/CT for diagnosing chondrosarcoma were revealed in the current study; meanwhile, the relatively narrower 95% confidence intervals (0.86-0.97 and 0.82-0.93, respectively) and smaller heterogeneity (I 2 = 15.69% and 0%, respectively) in comparison with those of 18 F-FDG PET indicated that these results were stable and persuasive.…”
Section: Discussionmentioning
confidence: 99%
“…Chondrosarcoma is the second most common primary malignant bone sarcoma characterized by the production of atypical cartilage matrix and invasive growth inside the pre-existing cortical and medullary bone tissue [1]. This malignant disorder could be further subcategorized to lowgrade (G1), intermediate-grade (G2), high-grade (G3), and dedifferentiated chondrosarcoma, which manifest diverse histological features and clinical behaviors [2].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation